Behaviour of Aquaporin Forward Osmosis Flat Sheet Membranes during the Concentration of Calcium-Containing Liquids - Alibek Omir; Aliya Satayeva; Aigerim Chinakulova; Arailym Kamal; Jong Kim; Vassilis J. Inglezakis; Elizabeth Arkhangelsky (Membranes, 2020)
This study aims to examine the scaling and performance of flat sheet aquaporin FO membranes in the presence of calcium salts. Experiments showed that the application of calcium sulphate (CaSO4) resulted in an 8–78% decline in the water flux. An increase in the cross-flow velocity from 3 to 12 cm/s reduced the decline in the flux by 16%. The deposition of salt crystals on the membrane surface led to the alteration in the membrane’s intrinsic properties. Microscopy, attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy, and X-Ray fluorescence (XRF) analyses confirmed measurements of the zeta potential and contact angle. The use of a three-salt mixture yielded severe scaling as compared with the application of calcium sulphate dehydrate (CaSO4 × 2H2O), i.e., a result of two different crystallisation mechanisms. We found that the amount of sodium chloride (NaCl), saturation index, cross-flow velocity, and flow regime all play an important role in the scaling of aquaporin FO flat sheet membranes.